Literature Review: The Effect of Extra Virgin Olive Oil (Olea europaea L.) on Pseudomonas aeruginosa Bacteria - Domu, Anugrah Julistiar Aksan; Syamsu, Rachmat Faisal; Karim, Marzelina; Hadi, Santriani; Arfah, Arni Isnaini (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: Olive oil, especially Extra Virgin Olive Oil (EVOO), which contains polyphenols and phytochemical compounds such as flavonoids and oleuropein, has long been utilized to enhance human health and exhibits potential antibacterial activity against Pseudomonas aeruginosa, an opportunistic pathogenic bacterium often responsible for severe infections and resistance to various antibiotics. Objective: To investigate the antibacterial properties of extra virgin olive oil (Olea europaea L.) against Pseudomonas aeruginosa. Method: A literature review study obtained from the internet, including theses, journals, textbooks, and e-books. The databases used were Google Scholar, Elsevier, ScienceDirect, and PubMed NCBI. Results: Extra Virgin Olive Oil (EVOO) demonstrates antibacterial activity against Pseudomonas aeruginosa based on findings from 10 journals. Bioactive compounds such as polyphenols, oleuropein, and hydroxytyrosol are effective against Pseudomonas aeruginosa through mechanisms that include inhibiting quorum sensing, damaging the cell wall, increasing membrane permeability, and inhibiting biofilm formation and virulence factors. Olive leaf extract and combinations with nanoparticles further enhance antibacterial effectiveness against resistant strains, making EVOO a potential natural antibacterial agent. Conclusion: Olive oil, particularly Extra Virgin Olive Oil (EVOO), contains bioactive compounds such as oleacein, oleocanthal, polyphenols, flavonoids, oleuropein, and hydroxytyrosol, which exhibit significant antibacterial activity against Pseudomonas aeruginosa.